Development of Hillchol®, a low-cost inactivated single strain Hikojima oral cholera vaccine. Issue 50 (25th November 2020) - Sharma, Tarun; Joshi, Neeraj; Kumar Mandyal, Ashwani; Nordqvist, Stefan L; Lebens, Michael; Kanchan, Vibhu; Löfstrand, Madeleine; Jeverstam, Frida; Mainul Ahasan, Mohammad; Khan, Imran; Karim, Mahbubul; Muktadir, Hasneen; et al.
Abstract: Cholera remains an important global health problem with up to 4 million cases and 140, 000 deaths annually. Oral cholera vaccines (OCVs) are now a cornerstone of the WHOs "Ending Cholera – A Global Roadmap to 2030" global program for the eventual elimination of cholera. There are currently three WHO prequalified OCVs available, Dukoral®, Shanchol® and Euvichol-Plus®. These vaccines are effective but due to a multiple strain composition and two different methods of inactivation, are complex and costly to manufacture. We describe here the characterization and industrial scale development of Hillchol®; a novel, likely affordable single-component OCV for low and middle-income countries. Hillchol® consists of formalin-inactivated bacteria of a stable recombinant Vibrio cholerae O1 El Tor Hikojima serotype strain expressing approximately 50% each of Ogawa and Inaba O1 LPS antigens. The novel OCV can be manufactured on an industrial scale at a low cost. Hillchol® was well tolerated in animal toxicology studies and shown to have non-inferior oral immunogenicity in mice for both intestinal-mucosal and serological immune responses when compared with a WHO-prequalified OCV. The optimized production of this single component OCV will reduce cost of OCV production and thus substantially increase vaccine availability. Based on these results, Hillchol® has been produced at a GMP facility and used successfully for clinical phase I/II studies.